KAJIAN TINGKAT KERUSAKAN ANAKAN TREMBESI (Samanea saman) AKIBAT SERANGAN HAMA DAN PENYAKIT DI SHADEHOUSE - Hasmiah Hasmiah; Ahmad Yamani; Susilawati Susilawati (Universitas Lambung Mangkurat, 2020)
The aim of this research is to know the frequency, intensity and level of damage which is caused by pests and diseases on Trembesi (Samanea saman) seedling in shade house. Based on the results, the frequency of pests and diseases attacks in shade house is 87 seedlings. Intensity of pests and diseases attacks on Trembesi in shade house is 46,26%. The level of damage on Trembesi seedlings due to pests and diseases in shade house, make a minor damage levels. Pests which attack Trembesi seedlings are green grasshopper, caterpillar and egg caterpillar. The diseases which attack Trembesi seedlings in shade house are leaf blotches, discoloration and fungus withered.Keywords: pests, diseases, trembesi, shade house